Rede de atenção psicossocial em saúde mental e as redes sociais dos usuários : estudo de caso em um município mineiro - Maria Aline Gomes Barboza (2018)
This research aims to analyze the interplay between the Network of Psychosocial Attention in Mental Health (RAPS) and the social networks of mental health users in the process of social insertion of these users, based on the study of the mental health network of the municipality of Ipatinga / MG. In the analysis of this interrelation, the institutional objectives of the RAPS were considered, which put it in the official discourse as the operator of psychiatric deinstitutionalization, the construction of new forms of sociability and social contractuality. It was tried to answer to what extent the insertion of the user in the RAPS can contribute, or not, to increase its capacity of constructing or reconstructing social networks of support. As a means and product of this research, we have also sought to analyze conceptions of territory and social networks in their centrality to theories that propose the psychosocial way of attention in mental health. Without disregarding the institutional and personal interfeasures in the data production context of this research, the methodological course was based on an interdisciplinary approach that integrates methods of ethnographic, cartographic and Social Network Analysis. The interrelation between RAPS and social networks in the process of social insertion of its users has proved to be complex and problematic in this case study, despite being highly desired by the actors involved in Psychosocial Care in Mental Health. The main impasses observed are related to the assistance model of the Municipal Mental Health Program, whose work processes give little priority to the interdisciplinary logic and the integrality of health care. Added to this is the strong local culture of valuing specialized knowledge and liberal practice in health, especially psychology, which favors little permeability of the institutional network to the diversification of collective and participatory practices. Strategies of permanent education, improvement of the work management of existing services and the creation of new devices are pointed out as outputs to such impasses. In the interrelationship of the institutional network with the users' social networks, the exchange of expected actions for each of these networks stands out, considering that family, friendship, neighborhood, religious and health care ties have specific functions in the insertion process of users. However, it is assessed that the interrelation between networks is still not very powerful in the process of social insertion of RAPS users.